Between Bikol and the Bard: Gode Calleja’s postcolonial Sinaramutan translation of Shakespeare’s Sonnets 18 and 29 - Santos, Maria Lorena M. (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper examines the translation praxis, called Sinaramutan, of Godehardo Calleja in his rendering of Shakespeare's sonnets for the Bikolnon (people from Bikol) in the southeastern Luzon region of the Philippines. Sinaramutan derives from the Bikol word simot, meaning gleanings or leftovers, while a related verb, saramutan, means to collect or to heap together many small items. In his Sinaramutan translations, Calleja mainly uses a base lexicon of the Bikol Central Standard dialect, to which he adds vocabulary from the languages and dialects of Bikol provinces, Catanduanes, Sorsogon, and Masbate; he occasionally borrows from Tagalog, the basis of the country’s national language or, more rarely from Philippine regional languages like Hiligaynon and Kinaray-a, related Austronesian languages of Southeast Asia, and Sanskrit. In doing this, he avoids words of Western origin, specifically from Spanish and English, the languages of former colonisers. The title of Calleja’s collection reflects the decolonising enterprise of his translation praxis: Kun Saná si Shakes Taga Satô, which means “If Shakes Were Just from Here.” This paper zooms in on translations of two well-known sonnets, 18 and 29, to harvest what it can from applying a Sinaramutan translation that localises and talks back to Shakespeare and a Bikolnon linguistic canon. The paper argues that Calleja's translation praxis does more than write back to the coloniser: It also defies both the regional centre and a monolithic Bikol language by cultivating a Bard who is Bikolnon, thus writing into Bikol a “Shakes” from here.